PROSPECT FOR ECOTOURISM SECTOR IN WANAGIRI VILLAGE DURING THE NEW NORMAL ERA - I Made Budayana; Nyoman Rasmen Adi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This research is aimed to know and understand the prospects of the sector of ecotourism Wanagiri village in a normal new era. To answer research questions, used conducted interviews with informants to understand the prospects of the ecotourism tourism sector in the new normal era. This study uses an ethnographic approach as a variant of the qualitative approach. The data analysis technique in this study was carried out in four steps: data collection, data reduction, data presentation (data display), and conclusion drawing/verification. The validity test of the data in this qualitative research includes the credibility test (credibility), data triangulation, member check, confirmability (objectivity) of the data. The results showed that: First, tourism in the pandemic era cannot run and stop the sector of tourism in Bali, especially in the village of Wanagiri. Wanagiri Village tourism is the value-added for the community's economy because the object of tourist-based nature is located in the village Wanagiri managed by a group of people under the supervision of the Department of Tourism District Buleleng and BKSDA (Agency for Conservation of Resources Power Nature). Encouraging children teens to create innovations to improve the Village Tourism in Rural Wanagiri and improve business locally. Strategy forward to increase the power interests of a Rural Tourism, which is Transport and Connectivity equipped with an extra value package developed by the Bureau of Travel Tourism for people who traveled effective, efficient, and productive.